PEMEROLEHAN BAHASA INDONESIA PADA SANTRI ASAL JERMAN DI SMP THURSINA IIBS MALANG - Arif Fatahillah F (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Language learning is based on the belief that a second language can only be acquired through a deliberate and conscious learning process. The development of second language acquisition is not only from local languages to Indonesian or Indonesian to English or vice versa. Foreigners who learn Indonesian are usually called (BIPA) Indonesian for Foreign Speakers. This research study is to describe the process of acquiring Indonesian as the second language of German students at Thursina IIBS Malang Junior High School. This research uses descriptive qualitative research which will describe in detail about the process of Indonesian language acquisition of German students at Thursina IIBS Junior High School in Malang. Where the source of data used is the German students themselves. The data collection procedure is taken by listening and interviewing the research subject. As a result, the Indonesian language acquisition of German students has been learnt before going to Indonesia. Upon arrival in Indonesia, German students acquire Indonesian from (a) the environment of the Thursina IIBS Malang boarding school and (b) from the BIPA subject class. Meanwhile, the ability to write free essays using Indonesian is still not fully perfect, because the influence of the Indonesian language received when outside the classroom is greater than when in the classroom.